Developing Digital Media Based on Local Wisdom to Increase Student Engagement in Social Studies Learning - Yuliantoro Yuliantoro; Dewi Liesnoor Setyowati; Thriwaty Arsal; Apik Budi Santoso (STAI Hubbulwathan Duri, 2025)
Student engagement in social studies learning at the junior high school level remains a challenge, often due to limited contextual teaching methods and conventional media. This study addresses the need for media innovation by developing digital learning materials that integrate local wisdom to enhance relevance and engagement. The research employed a Research and Development (RD) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The media was designed using content on local wisdom—hutan larangan and sungai larangan—and developed through Canva and Heyzine platforms into interactive digital formats. Expert validation was conducted for content and media design. Implementation involved two trials: a small group (40 students) and a large group (92 students). Data were collected through questionnaires assessing feasibility and student engagement. Expert validation rated the media as highly feasible, with scores of 94% (content) and 95% (media design). Student responses were also highly positive, scoring 90% in the small group and 92% in the large group. Student engagement significantly improved, rising from 60% to 90% in the small group and from 62% to 93% in the large group following media implementation. The findings demonstrate that digital media based on local wisdom effectively increases student engagement in social studies learning. The integration of culturally relevant content and interactive design fosters greater interest and participation, suggesting strong potential for broader application in educational settings.